Analisa Pengendalian Kualitas Produk Dengan Menggunakan Statiscal Processing Control (SPC) Di PT KLX - Meylia Vivi Putri; Albertus L. S.; Khoerun Nisa Safitri; Riski Arianto Harahap (LPPM Politeknik Jambi, 2022)
A company cannot be separated from consumers and the products it produces. Consumers certainly hope that the goods they buy will be able to meet their needs and desires so that consumers hope that the product has good and guaranteed conditions. Therefore, companies must see and maintain that the quality of the products produced is guaranteed and accepted by consumers and can compete in the market. This study is intended to analyze whether the resulting product is not in accordance with the specified product quality standards and analyze what factors cause product defects. The study was conducted at PT. KLX for 30 days as many as 6000 pipes taken chatter, step, burs defect data using statistical processing control (SPC). The results of this study conclude that based on the P-Chart analysis that has been carried out at PT KLX, there are 3 types of defects that occur in threaded pipe products, namely chatter defects, step defects, and burs defects. So the products produced by PT KLX do not meet the quality standards that have been determined by the company, the factors that cause product defects are in accordance with the fishbone causal diagram, namely workers (people), raw materials (materials), machines (machine), Method (method).